STRATEGI RELAKSASI UNTUK MEMBANTU SISWA YANG MENGALAMI STRES BELAJAR DI KELAS 9D SMP NEGERI 1 MEJAYAN KABUPATEN MADIUN - Bambang Agus Pramunto (Universitas PGRI Madiun, 2015)
Along with the advancement of science and technology, the problems facedby individuals increasingly complex. A problem that can not be avoided bystudents in general and students in grade 9 in particular is a matter of learning.Slowly but surely grade 9 students have to face the